KUALITAS SENSORI, UKURAN PORI, INDEKS GLIKEMIK, DAN BEBAN GLIKEMIK ROTI TAWAR SUBSTITUSI TEPUNG SINGKONG (MANIHOT ESCULENTA) DAN TEPUNG TEMPE[Sensory Quality, Pore Size, Glycemic Index, and Glycemic Load of White Bread with Cassava Flour (Manihot esculenta) and Tempeh Flour Substitution] - Nanik Hamidah; Riyanto Riyanto; Endang Taat Uji (Universitas Airlangga, 2019)
Bread is alternative food made by wheat fl our that can be used as one of carbohydrates sources. Bread is classifi ed as high glycemic index food. Cassava is one of carbohydrate source contain high resistant starch which has low glycemic index, meanwhile tempeh has high protein value. Substitution of wheat fl our with cassava and tempah fl our is predicted can give lower glycemic index and higher protein content of white bread. Purpose for this research was to analyse the effect of cassava fl our tempeh fl our substitution to sensory, pore size, glycemic index, and glycemic load of white bread. Research method were used true experimental with complete randomized design. Proportion of cassava and tempeh fl our were respectively P1 (0%), P2 (2.4%;0.8%), P3 (4.8%;1.6%), P4 (7.3%;2.4%) and P5 (9.7%;3.2%). Sensory quality and pore size were analysed by Kruskall Wallis followed by ranking difference test. Glycemic index test were done only for the best formula (P2) based on sensory test treatment. Result of this study showed substitution of cassava and tempeh fl our gave signifi cant infl uences toward sensory quality including texture (p=0.003), fl avour (p=0.0001), colour [crumb, crust (p=0.0001)], taste (p=0.012), and size of pore (p=0.0001). Glycemic Index (IG) and Glycemic Load (BG) test of formula P2 showed 132.32 and 53,32 which belong to high category. Substitution of wheat fl our with cassava and soybean tempeh fl our changed the sensory quality, pore size, IG and BG high category